Two visual systems in Molyneux subjects. - Ferretti, Gabriele (Phenomenology & the Cognitive Sciences, 2018)
Molyneux’s question famously asks about whether a newly sighted subject might immediately recognize, by sight alone, shapes that were already familiar to her from a tactile point of view. This paper addresses three crucial points concerning this puzzle. First, (a) the presence of two different questions: the classic one concerning visual recognition and another one concerning vision-for-action (the second question has been almost completely neglected in the literature and even those who mention this second formulation do not fully investigate it). Second, (b) the explicit distinction, reported in the literature, between ocular and cortical blindness. Third, (c) the importance of making reference to our best neuroscientific account on vision, ‘the two visual systems model’, in order to better address Molyneux’s problem(s). Then, by offering a new, deeper analysis of the relation between (a), (b) and (c), this paper suggests that the subjects of Molyneux’s two different questions show the same visual impairment as brain-damaged subjects with different lesions of the visual cortex. In particular, the subject of the first (classic) question shows the same impairment in visual recognition as a visual agnosic subject, while the subject of the second question shows the same visual impairment in visuomotor processing as an optic ataxic subject. These impairments still hold even if ocular processing is restored. Therefore, I suggest the following. For the first classic question, the required experimental setting cannot be properly reached. By contrast, concerning the second question, based on the interpretation we select, either the answer is negative, or, as with the first question, the experimental setting cannot be properly reached. This proposal constitutes, with the other approaches offered in the literature, a further attempt to tackle the enormous complexity of Molyneux’s puzzle.